Obstetric Outcomes in Patients Treated for Deep Pelvic Endometriosis. Issue 2 (April 2014) - Saccardi, Carlo; Borghero, Angela; Gizzo, Salvatore; Codroma, Anna; Perini, Francesca; Luisi, Stefano; Litta, Pietro
Purpose: The aim of this study was to assess obstetric outcomes and symptoms during and after pregnancy in women submitted to surgical treatment for deep pelvic endometriosis. Methods: We evaluated 123 women who underwent surgery for severe deep pelvic endometriosis-related symptoms. Interventions were excision of rectovaginal septum nodule with or without rectal or vaginal resection, or excision of nodule of uterosacral ligaments. On the basis of pregnancy desire, patients were submitted to a telephone interview and asked if there had been a pregnancy and its outcome. They were also asked to describe their pain symptoms before, after and during the pregnancy. Results: From the 123 patients, we selected 43 women desiring pregnancy after surgery, who answered the telephone interview. Twenty-four patients (55.8%) got pregnant. We recorded 34 pregnancies a mean 21.8 ± 17.9 months after surgery. In the group of 25 full-term pregnancies, 14 women (56%) had a vaginal delivery without complications, and 11 (44%) underwent a cesarean section. In only 3 cases, was the indication of cesarean section related to previous surgery. Seventy-one percent of women treated without rectal or vaginal resection delivered vaginally. We also registered 1 case of uncomplicated vaginal delivery in a patient with vaginal resection and another 1 in a patient with rectal resection. In the patients who complained of pain before pregnancy, we observed a resolution of pain symptoms during pregnancy, but after delivery these symptoms reappeared. Conclusions: In patients submitted to surgery for deep pelvic endometriosis, even in cases of vaginal or rectal resection, a cesarean section is not always mandatory.